2017
DOI: 10.1016/j.bbr.2016.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Altered cytokine profile, pain sensitivity, and stress responsivity in mice with co-disruption of the developmental genes Neuregulin-1×DISC1

Abstract: The complex genetic origins of many human disorders suggest that epistatic (gene×gene) interactions may contribute to a significant proportion of their heritability estimates and phenotypic heterogeneity. Simultaneous disruption of the developmental genes and schizophrenia risk factors Neuregulin-1 (NRG1) and Disrupted-in-schizophrenia 1 (DISC1) in mice has been shown to produce disease-relevant and domain-specific phenotypic profiles different from that observed following disruption of either gene alone. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In addition, multiple studies have indicated that neuroinflammation, whose importance on neuropathic pain has been shown previously, can yield important insights into the function of Nrg1‐ErbB signaling. For instance, a recent study showed that mice with Nrg1 mutation display decreased pain sensitivity accompanied by decreased basal proinflammatory cytokine levels . In addition, in vivo and in vitro experiments also showed that microglia can be activated when Nrg1 combines with the ErbB2 receptor on the microglial membrane and that the activated microglia can release IL‐1β .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, multiple studies have indicated that neuroinflammation, whose importance on neuropathic pain has been shown previously, can yield important insights into the function of Nrg1‐ErbB signaling. For instance, a recent study showed that mice with Nrg1 mutation display decreased pain sensitivity accompanied by decreased basal proinflammatory cytokine levels . In addition, in vivo and in vitro experiments also showed that microglia can be activated when Nrg1 combines with the ErbB2 receptor on the microglial membrane and that the activated microglia can release IL‐1β .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study showed that mice with Nrg1 mutation display decreased pain sensitivity accompanied by decreased basal proinflammatory cytokine levels. 22 In addition, in vivo and in vitro experiments also showed that microglia can be activated when Nrg1 combines with the ErbB2 receptor on the microglial membrane and that the activated microglia can release IL-1β. 6 The trigger function of Nrg1 in microglia activation has also been validated in several other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the complement system triggers inflammation, whereas Nrg1 is anti-inflammatory, implying a counter regulatory relationship between Nrg1 and C4 signaling. 44,57 Altered cytokine profiles in the plasma, spleen, and brain have been demonstrated in Nrg1 HET mice, 46,58 which may then impact upon C4 expression. 59,60 It is noteworthy, that in humans a loss-of-function mis-sense mutation in NRG1 increased plasma levels of numerous autoimmune and inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Neuregulin 1 ( NRG1 ) is a well-established genetic risk factor for schizophrenia ( Mostaid et al, 2016 ), and a mutation in the transmembrane domain region of NRG1 is found in patients with schizophrenia ( Walss-Bass et al, 2006 ). A multitude of previous studies, including from our team, have established face, construct, and predictive validity for Nrg1 transmembrane domain heterozygous ( Nrg1 TM HET) mice (review: Karl, 2013 ), which exhibit age-dependent and sex-specific differences in locomotion, sensorimotor gating and social behaviors ( Karl et al, 2007 ; van den Buuse et al, 2009 ; Desbonnet et al, 2017 ) changes to glutamatergic and GABAergic signaling and inflammatory tone ( Desbonnet et al, 2012 ; Long et al, 2012 ; Newell et al, 2013 ; Chohan et al, 2014 ) as well as altered sensitivity to THC ( Boucher et al, 2007 ; Long et al, 2013 ), reflecting findings in clinical cohorts ( Saha et al, 2005 ; Han et al, 2012 ). Specifically, Nrg1 TM HET males exhibit hyperlocomotion in the open field ( Karl et al, 2007 ), deficits in social interaction (SI) ( O’Tuathaigh et al, 2008 ), and deficits in prepulse inhibition (PPI) ( Stefansson et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%